Fireflies! - Brinckloe, Julie (Nnnew York Aladdin Paperbacks, 1985)
A young boy is proud of having caught a jar full of fireflies, which seems to him like owning a piece of moonlight, but as the light begins to dim he realizes he must set the insects free or they will die.
K - 2
Keywords: Fireflies - Fiction